The Environmental Impacts of the Trans-Java Toll Road Infrastructure Project - Ririn Yuliatiningsih; M. Halley Yudhistira (Eduvest - Journal of Universal Studies, 2026)
The research aims to analyze the operational impact of the Trans Java toll road on the quality of the environment in districts/cities on the island of Java during 2012–2024. Three environmental indicators are the Air Quality Index (IKU), the Environmental Quality Index (IKLH), and carbon emissions. The method used is Difference-in-Differences with Two-Way Fixed Effects regression and Dynamic Analysis. Nationally, the operational impact of toll roads does not show significant effects on KPIs, IKLH, or carbon emissions, indicating that environmental impacts are contextual. Spatial analysis revealed a significant decline in air quality in Central Java, the main corridor of the Trans Java network, consistent with the theory of network centrality in which high-traffic areas bear greater environmental externalities. Topographic characteristics, such as basins and valleys, exacerbate environmental vulnerability by limiting the spread of pollutants. These findings emphasize the need for the government to consider spatial heterogeneity and topographic variables in the construction of toll roads. This research opens up opportunities for further studies on the environmental impact of toll roads over a longer period of time and a more detailed approach.